REGULARITIES IN THE FORMATION OF THE COMPETITIVE LANDSCAPE OF THE EMERGING HIGH-TECH MARKETS - V. G. Zinov; L. A. Tsvetkova (Ekonomika Nauki)
The problem of identification of key actors of scientific and technological development of the Russian Federation is considered. Attention is drawn to the absence of domestic companies interested and ready to cofinance R & D in many promising areas. The analysis of the map of the competitive landscape of the technological area “the reprogramming of somatic cells”, the development of which is expected to create the industry of artificial human organs, has been carried out. It has been shown that large transnational companies need 3–5 years to incorporate new technology into their marketing strategy and become a leader in the emerging market of high-tech goods and services.